Influence of late fluid management on the outcomes of severe trauma patients: A retrospective analysis of 294 severely-injured patients. Issue 9 (September 2017) - Mezidi, Mehdi; Ould-Chikh, Mehdi; Deras, Pauline; Maury, Camille; Martinez, Orianne; Capdevila, Xavier; Charbit, Jonathan
Abstract: Background: Liberal late fluid management (LFM) is associated with higher morbi-mortality in critically ill populations. The aim of the study was to assess the association between LFM and duration of mechanical ventilation in a severe trauma population. Methods: A retrospective analysis of consecutive patients with an ISS ≥ 16 and a length of stay in the intensive care unit (ICU) ≥ 7 days was performed. The conservative LFM group included patients with at least 2 consecutive days with a negative fluid balance between day 3 and day 7; other patients were allocated to the liberal LFM group. Results: 294 severely injured patients were included, 157 (53%) as conservative LFM and 137 (47%) as liberal LFM. The groups did not differ significantly in terms of baseline characteristics, severe injuries, severity criteria or transfusion needs. Liberal LFM was significantly associated with more ventilation days (11 vs 8.5 days; P = 0.02), less ventilator-free days at day 30 (19 vs 21 days; P = 0.03), longer ICU stay (19 vs 16 days; P = 0.03) and longer hospital stay (30 vs 25 days; P = 0.04). Mortality rates were comparable between groups (6%). Liberal LFM was significantly associated in multivariable analysis with a reduced number of ventilator-free days at day 30 (β = − 2.14 [95% CI, −4.2 to −0.08], P = 0.042). Conclusions: Liberal LFM was associated with higher morbidity in severe trauma patients, longer duration of ventilation, and longer ICU and hospital stays. These results were observed despite similar severity on admission and early fluid management.